COMPARATIVE STUDY OF PERSONALITY WITH AYURVEDIC PRAKRITI - Prasuna, V. V. L.; Sharma, Bhuvnesh Kumar; Narayana, Ala (International Journal of Ayurveda and Pharma Research, 2015)
Study of personality is one of the most fascinating sciences that attracted many researchers world wide. Personality is a dynamic and organized set of characteristics possessed by a person that uniquely influences his or her cognitions, emotions, motivations, and behaviors in various situations. The study of personality in modern psychology dates back to ancient Greek, when Plato, Aristotle and Hippocrates suggested their theories on personality. Through the centuries, their theories have evolved, changed and have continued to be the base and foundation of modern psychology. As centuries progressed, many philosophers, psychologist and physicians have expanded this field. Personality theories such as type, trait, humanistic, behaviorist, psychoanalytic, cognitive and psychobiologist theories have emerged from ancient times and continue to be present in modern times. Ayurvedic system of medicine is one of the ancient systems of medicine, which recognizes the individuality of an individual by means of Prakriti. Prakriti can be correlated as psycho-somatic constitution, Because Ayurveda believes that human organism behaves in a wholesome and complex manner and physical and mental factors of personality cannot be isolated. Ayurveda gives eloberated description about prakriti in terms of predominance of body humor, nature of sperm and ovum, season and condition of the uterus, food and regimen of mother, composition of Pancamahabhuta and how it getsinfluenced by race/religion, caste/family, habitat, nature of the season, age or stages of life and basic instincts. This way Ayurveda provides a comprehensive, multiphasic and multidimensional theory of personality, which gives a complete picture of an individual. This paper aims to study ayurvedic perspective of personality.